2022
DOI: 10.1111/bjet.13255
|View full text |Cite
|
Sign up to set email alerts
|

The information won't just sink in: Helping teachers provide technology‐assisted data literacy instruction in social studies

Abstract: In this study, support for teaching data literacy in social studies is provided through the design of a pedagogical support system informed by participatory design sessions with both pre‐service and in‐service social studies teachers. It provides instruction on teaching and learning data literacy in social studies, examples of standards‐based lesson plans, made‐to‐purpose data visualization tools and minimal manuals that put existing online tools in a social studies context. Based on case studies of eleven pra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 77 publications
0
6
0
Order By: Relevance
“…Interpreting data visualizations can be intimidating without context/content understanding (Shreiner and Guzdial, 2022). Most statistics classes present data with minimal context; however, data derives meanings from contexts and interpreters (Acker and Bowler, 2018).…”
Section: Personally Meaningful Data Literacy Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Interpreting data visualizations can be intimidating without context/content understanding (Shreiner and Guzdial, 2022). Most statistics classes present data with minimal context; however, data derives meanings from contexts and interpreters (Acker and Bowler, 2018).…”
Section: Personally Meaningful Data Literacy Researchmentioning
confidence: 99%
“…Data visualization and visualization literacy are also crucial components of any definition of data literacy (Deahl, 2014; Rubin, 2020). Visualizations enhance students’ comprehension and reasoning of complex phenomena by offering contextually-rich information for explanation and argumentation (Roberts et al , 2014; Shreiner and Guzdial, 2022). Researchers designing visualizations to support students in extracting and interpreting data patterns have found that visualization literacy facilitates data literacy development (Alper et al , 2017; Bishop et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Social studies as a context for data science is explored in Shreiner and Guzdial's (in press) paper. This study described using open educational resources and data visualization tools for supporting teachers in their efforts to teach data literacy in social studies and history classrooms.…”
Section: Contributions To the Special Sectionmentioning
confidence: 99%
“…While there is doubtless value in coming to similar findings despite using different research approaches, there is also value in different approaches to researching data science learning. We have found it beneficial to consider essential research by scholars not only with backgrounds in computer science and statistics education, for example, but also in the arts (Matuk et al, 2022), humanities (Vance et al, 2022), social studies (Shreiner & Guzdial, 2022), and everyday life and experiences (Gebre, 2022;Radinsky & Tabak, 2022;Vacca et al, 2022). Other scholars have argued for the importance of a broadly humanistic approach to data science education, one that recognizes that questions about who uses data overlap with questions about who has value and power (V. Lee et al, 2021;Philip et al, 2016).…”
Section: How Can We Generate a Deeper Understanding Of Data Science L...mentioning
confidence: 99%